Pengaruh pemberian pupuk bokashi terhadap produksi rumput gajah (Pennisetum purpureum). - Kastalani Kastalani; Maria Erviana Kusuma; Septi Melati (Fakultas Peternakan Universitas Kristen Palangka Raya, 2016)
The aim of this research was to know the effect of bokashi fertilizer application on the production of Elephant grass (Pennisetum purpureum). This research was design by using Completely Random Design (CRD) with single factor experiment that is doses bokashi (B), with the level of each doses, b0= control (without bokashi), b1= 10 ton ha-1, b2= 20 ton ha-1, b3= 30 ton ha-1. The result showed that the applications bokashi giving the influence to production of Elephant grass. Bokashi 30 ton ha-1 gives the highest production of Elephant grass. Key words : Bokashi, doses, elephant grass, production